2021
DOI: 10.1101/2021.06.12.21258810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibody Responses to SARS-CoV-2 after Infection or Vaccination in Children and Young Adults with Inflammatory Bowel Disease

Abstract: Background: Characterization of neutralization antibodies to SARS-CoV-2 infection or vaccination in children and young adults with inflammatory bowel disease (IBD) receiving biologic therapies is crucial. Methods: We performed a prospective longitudinal cohort study evaluating SARS-CoV-2 Spike protein receptor binding domain (S-RBD) IgG positivity along with consistent clinical symptoms in patients with IBD receiving infliximab or vedolizumab. Serum was also obtained following immunization with approved vaccin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…The vast majority of included studies evaluated vaccines developed by Pfizer (BNT162b2) or Moderna (mRNA-1273). Thirteen studies included patients who received the vaccine developed by Janssen (Ad26.COV2.S) [ [25] , [26] , [27] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ], nine included patients vaccinated with the AstraZeneca vaccine (ChAdOx1) [ [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ], three included patients receiving the CoronaVac vaccine (Sinovac Biotech) [ [50] , [51] , [52] ], and one randomized controlled trial evaluated the vaccine developed by Novavax (NVX-CoV2373) vaccine [ 53 ]. One study included patients receiving the BBV152-Covaxin (Bharat Biotech) vaccine [ 44 ] and one included patients receiving the BBIBP-CorV (Sinopharm) vaccine [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The vast majority of included studies evaluated vaccines developed by Pfizer (BNT162b2) or Moderna (mRNA-1273). Thirteen studies included patients who received the vaccine developed by Janssen (Ad26.COV2.S) [ [25] , [26] , [27] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ], nine included patients vaccinated with the AstraZeneca vaccine (ChAdOx1) [ [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] ], three included patients receiving the CoronaVac vaccine (Sinovac Biotech) [ [50] , [51] , [52] ], and one randomized controlled trial evaluated the vaccine developed by Novavax (NVX-CoV2373) vaccine [ 53 ]. One study included patients receiving the BBV152-Covaxin (Bharat Biotech) vaccine [ 44 ] and one included patients receiving the BBIBP-CorV (Sinopharm) vaccine [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-one studies reported immunogenicity in 4680 patients with inflammatory immune-mediated diseases ( Table S6 ) [ 27 , 28 , 32 , 36 , 37 , 39 , [45] , [46] , [47] , 50 , 51 , 54 , 55 , 82 , [161] , [162] , [163] , [164] , [165] , [166] , [167] , [168] , [169] , [170] , [171] , [172] , [173] , [174] , [175] , [176] , [177] , [178] ]. Main represented groups included rheumatoid arthritis ( n = 665), inflammatory bowel diseases ( n = 476) and multiple sclerosis ( n = 231).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, SARS-CoV-2 serological tests were mostly evaluated in adults, so we have limited knowledge of pediatric patients. The studies that compared antibody levels of both children and adults are limited [11][12]. Recently, evidence of natural immunity to SARS-CoV-2 in children has drawn attention as a parameter that may help diagnose multisystem inflammatory syndrome in children (MIS-C or MIS-A in adults) [13].…”
Section: Introductionmentioning
confidence: 99%